(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyses a bronze coin from ildiŕda with the inscription erder that weights 8.2 gr. and displays in one face a schematic masculine figure and a walking wolf in the other. The coin is identified as a semis, because presents a half-moon, the distinctive mark of the semis in ildiŕda coins, and because de text erder is part of the value mark of the semis of undikesken and the hemidrachma of ars. The use of erder as a value mark with a value of ½ and the presence of erder and erdi in texts over lead plaques in favourable contexts to the presence of quantitative expressions, provide evidence about the correctness of a recent proposal that identifies as numbers some Iberian lexemes, because his resemblance to Basque numbers, among them ‘erdi’ (half).